Emerging Trends in Data Mining- An Algorithms used, Challenges and its Significance in Current Scenario - Gurung, Gagan; Shah, Rahul; Prasad Jaiswal, Dhiraj (International Journal of Computer Sciences and Engineering, 2020)
Data is defined as the collection of facts. When data are refined it becomes information. Data plays a vital role in obtaining any kind of information. These data are collected from different sources. It is difficult to handle these data sometimes. In data mining, all the data are collected from different sources as per their need. From telecommunication to retail industries, from finance to educational institutes all these data give vital information for any kind of execution that needs to be done for the future course of action. However, some challenges need to be taken care of while obtaining these data. Some data might be noisy, some might be scattered. Looking into this scenario we should be very careful while playing with these data. Every organization heavily depends on these data for their planning and execution. Data mining plays a vital role in achieving the target of the organization. It should be handled in a precise manner. Though the challenges are many their significance is equally high. This paper explains the brief ideas on what are the new trends in data mining and how it is helping to overcome our needs as per the current requirements.